On Lacunary Statistical Convergence of Order ? of Difference Sequences of Fractional Order - Aral, Nazlim Deniz; Et, Mikail (Amer Inst Physics, 2019)
The purpose of this paper is to introduce the concepts of Delta(alpha)-lacunary statistical convergence of order beta(0 < beta <= 1) with the fractional order of alpha and Delta(alpha)-lacunary strongly convergence of order beta with the fractional order of alpha. We establish some connections between Delta(alpha)-lacunary strongly convergence of order beta and Delta(alpha)-lacunary statistical convergence of order beta.
3rd International Conference of Mathematical Sciences (ICMS) -- SEP 04-08, 2019 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Difference sequence; statistical convergence; lacunary sequence